Shipment consolidation by terminals and vehicles - González-Ramírez, Rosa G. (2009)
This project designs and implements a new module in a logistics analysis tool called ”Logistika” that was developed by some graduate students in ASU. Initially, Logistika only had available a “Plant location module”, but this work makes an extension to include a new module that is called “Shipments Consolidation module”. The objective of the module is to determine the best distribution strategy for products manufactured in Mexico to customers located in US. The tool explores two consolidation strategies: by vehicles and terminals, so as to minimize the transportation and in transit inventory costs incurred. It also considers that it is desired to locate a consolidation center in Mexico for which the best location must be found.